Preliminary study on the occurrence of intestinal parasites in Malayan tapir (Tapirus indicus) in Zoo Negara, Malaysia - Mustapa, Muhamad Syahir; Ismail, Ahmad; Rahman, Faid; Ramli, Mat Naim (Institute for Tropical Biology and Conservation, Universiti Malaysia Sabah, 2014)
A preliminary study was conducted to investigate the occurrence of intestinal parasites in the faeces of captive Malayan tapir in Zoo Negara, Malaysia. A total of 12 fresh faecal samples were collected from three different individuals and screened for eggs and larvae using the sedimentation technique. The results shows that Strongylussp. infection was the highest with 43%, followed by Strongyloides sp. and Fasciolasp. with 17% each, Balantidiumsp. 11%, Ascarissp. 9% and unidentified 3%. Fasciolasp. and Ascarissp. were found in samples obtained from one individual kept in a cage while Balantidiumsp. was found in the free-roaming individuals. Previous information on parasitic diseases in tapir waslargely derived from those found in the wild. This study highlights the first record on parasitic infection in captive tapir in Malaysia. In addition, due to pathogenic importance of the parasites to both animals and humans, the population should be closely monitored. Considering the endangered status of the Malayan tapir, further studies are neededto highlight this issue.